Probabilistic human health risk assessment of commercially supplied jar water in Gopalganj municipal area, Bangladesh - Brahma, Partha Pratim; Akter, Sharmin; Haque, Md. Morshedul; Khirul, Md. Akhte (Frontiers in Water, 2024)
Every day, the amount of quality fresh water decreases notably due to contamination of drinking water. As a result, people use commercially supplied jar water in the southern part of Bangladesh as well as in the Gopalganj municipal area. This study aims to investigate the physicochemical parameters, trace elements, and microbial parameters for assessing human health risks from oral ingestion of these elements. This study gathered commercially supplied jar water samples from 15 companies in the Gopalganj municipal area during the post-monsoon season. Temperature, potential of hydrogen (pH), total dissolved solids (TDS), electrical conductivity (EC), and salinity showed significant variation among the samples, and the level was within the national and international standard limits. The concentrations of iron (Fe) and arsenic (As) were measured using a UV–VIS spectrophotometer and atomic absorption spectroscopy (AAS), respectively. The microbial analysis was conducted by the membrane filtration method. The study found that the water samples had an average concentration of 0.16 mg/L in terms of Fe and 0.016 mg/L in terms of As, with the mean value of As exceeding the standard limits. On the other hand, the mean Fe concentration value did not exceed the standards. Probable human health risk from heavy metal in the jar water was determined by hazard quotient (HQ), hazard index (HI), and carcinogenic risk (CR) assessments. A child (HI = 3.5914) is more vulnerable to non-carcinogenic human health risks than an adult (HI = 1.6931). Furthermore, pollution in water samples was found to pose a high carcinogenic risk, with children (CR = 1.6 × 10−3) being more vulnerable to carcinogenic risk than adults (CR = 7.5 × 10−4). In the microbial analysis, 100% of the samples exceeded the total coliform and fecal coliform standard limits, and 80% of the samples exceeded the Escherichia coli standard limits. Among the samples, 7% present high risk, around 47% present medium risk, 26% show low risk, and 20% show no risk based on the E. coli standard limits. This study did not find any samples that exceeded the extremely high limit for E. coli concentration. This study found that drinking jar water samples had inadequate quality, which may increase the risk of water-borne infections such diarrhea as well as heart disease, diabetes, and cancer. As a result, the manufacturer of drinking water in jars must carry out the essential quality control procedures, and the government should regularly monitor the procedures.